Strategi Guru Pendidikan Agama Islam Dalam Menghadapi Kemampuan Daya Serap Peserta Didik Di SMP Negeri 4 Sojol Kec. Sojol Kab. Donggala - Iksan Kahar (LPPM IAIN Sorong, 2020)
This paper discusses about the strategies of Islamic Religious Education teachers in dealing with students absorption skills. This study used qualitative research methods. Data collection techniques through observation, interviews and documentation. The data analysis technique used was data reduction, data presentation and data verification. This paper found that the Islamic religious education teacher at SMP Negeri 4 Sojol Kec. Sojol Kab. Donggala is successful in using learning strategies to increase thinking skills, because it can create fun learning and make students feel faster in understanding the subject matter of Islamic Religious Education. One aspect that affects the success of learning is the ability of the teacher to manage learning. The teacher delivering material learning with calm, not rushing in delivering material. So, the students can analyze the material. Creating a pleasant learning atmosphere in the classroom, making students not feel bored with the material